2008
DOI: 10.1155/2008/345895
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Catalytic Performance of Niobic Acid Dispersed over Titanium Silicalite

Abstract: Niobic acid, Nb 2 O 5 ·nH 2 O, has been supported on the titanium silicalite by impregnation method. The obtained materials were characterized by X-ray diffraction, infrared, and ultra-violet-visible diffuse reflectance spectroscopy, temperature programmed reduction, pyridine adsorption, and field emission scanning electron microscopy techniques. It was demonstrated that the tetrahedral titanium species still retained after impregnation of niobic acid. The results revealed that niobium species interacted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The same figure displays also the spectrum of Al 2 (WO 4 ) 3 as a reference for the tetrahedrally coordinated W atoms against oxygen. Its UV-Vis spectrum contains only one maximum typical for the presence of isolated tetrahedra (WO 4 ) [52,63,64]. As it is seen from Fig.…”
Section: Structural Analysismentioning
confidence: 91%
“…The same figure displays also the spectrum of Al 2 (WO 4 ) 3 as a reference for the tetrahedrally coordinated W atoms against oxygen. Its UV-Vis spectrum contains only one maximum typical for the presence of isolated tetrahedra (WO 4 ) [52,63,64]. As it is seen from Fig.…”
Section: Structural Analysismentioning
confidence: 91%
“…Crystalline niobic acid and NbOPO4 possess very low surface areas (<12 m 2 /g) 22 and, also niobium is an expensive metal and its limited availability on earth limits its use in industrial applications. Several researchers attempted to increase its surface area in order to increase the number of available acid sites either by trying to make the material porous and amorphous or disperse it over porous carriers [23][24][25][26] . Zhang et al, prepared mesoporous NbOPO4 in the presence of cetyltrimethylammonium ammonium bromide (CTAB) with varying p H conditions and obtained porous amorphous material with maximum surface area of 290.1 m 2 /g 27 Mal et al, used a supramolecular templating mechanism and used different templates thus obtaining a porous niobium phosphate with a maximum surface area of 482m 2 /g [28][29] .…”
Section: Hydroxyalkylation/ Hydrodeoxygenationmentioning
confidence: 99%
“…Barrows et al [6] found the effects of Nb on ZSM-5 where it was observed the change of structural property of HZSM-5 at different percentage of Nb impregnation. The characterization and catalytic performance of niobic acid dispersed over titanium silicate was investigated in 1-octene epoxidation [7]. Moreira et al [8] explained the nature and position of cerium in Ce-loaded Y zeolite and determined the catalytic performance in 2-propanol dehydration.…”
Section: Introductionmentioning
confidence: 99%